Case Report: Clinical and Pathological Findings of a Recurrent C3 Glomerulopathy With Superimposed Membranoproliferative Glomerulonephritis Pattern and Cryoglobulinemia Associated With COVID-19 - Daneshgar, Nastaran; Liang, Peir-In; Michels, Christina J.; Nester, Carla M.; Harshman, Lyndsay A.; Dai, Dao-Fu (Frontiers in Pediatrics, 2022)
Coronavirus disease 2019 (COVID-19) may cause a wide spectrum of kidney pathologies. The impact of COVID‐19 is unclear in the context of the complement system abnormalities, including C3 glomerulopathy (C3G). In this report, we describe a young adult receiving a kidney transplant for C3 glomerulopathy (C3G), a disorder of the alternative complement pathway. The patient developed a recurrent C3G approximately 7 months after transplantation. His post-transplant course was complicated by SARS-CoV-2 infection. There was a progression of glomerulonephritis, characterized by de novo immune-complex mediated membranoproliferative glomerulonephritis pattern of injury with crescentic and necrotizing features, along with positive immunoglobulins, persistent IgM staining and the presence of cryoglobulinemia. COVID-19 may have aggravated the inherent complement dysregulation and contributed to cryoglobulinemia observed in this patient. Our study of 5 sequential kidney allograft biopsy series implicates that COVID-19 in this patient promoted a superimposed immune complex-mediated glomerulonephritis with membranoproliferative glomerulonephritis (MPGN) pattern and cryoglobulinemia, which was a potentiating factor in allograft loss. This work represents the first report of cryoglobulinemic GN after COVID-19.